Assessment of mobile payment service based on user review in Indonesia - Dewi, Intan Novita; Nurcahyo, Rahmat; Farizal (Communications in Humanities and Social Sciences, 2024)
This study evaluates user satisfaction with mobile payment services, focusing on sentiment of user reviews from Twitter. Four key dimensions—reliability, economic benefits, assurance, and responsiveness—were analyzed for two applications, DANA and LinkAja. This study used Support Vector Machine algorithm with an accuracy measurement using the Confusion Matrix reaching 83.83% for DANA and 82,58% for LinkAja. The ROC curve showed the best AUC result of 0.909 for DANA and 0.900 for LinkAja (Excellent Classification). Sentiment analysis revealed that both applications faced predominantly negative sentiment, except for the economic benefit dimension of LinkAja, which showed a higher proportion of positive sentiment. Major issues identified include slow problem resolution, unresponsive customer service, and occasional application errors. These challenges highlight user dissatisfaction and the need for improved customer service and system reliability. The findings underscore the importance of addressing user complaints promptly to enhance satisfaction and foster loyalty.